KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MALANG (Studi pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Kabupaten Malang) - Adelia Shabrina Prameka; Nur Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Kabupaten Malang was given opportunity to explore the potential of financial resources by setting taxes and charges for the region to increase the acceptance of PAD. The research aims to analyze the contribution and effectiveness local taxation and charges to the PAD of Kabupaten Malang during the last five years (2007-2011). The object in this research is an area of Kabupaten Malang, research focusing to discuss about the PAD, local taxation, and local charges. Research type in this study was a descriptive. Analysis of local taxation and local charges to the PAD in the research carried out using the contributions analysis tax and charges to the total PAD each year and the effectiveness ratio of targets and realization. The results of this research found that average contribution local taxation and local charges type in receipt PAD Kabupaten Malang during 2007-2011 is greatly fluctuates. The biggest tax contributions comes from street lighting tax, averaging 36,4% over five years. As for the largest local charges contribution comes from public services charges, averaging 22,73% over five years. The larger percentage of contribution of a local tax and local charges to the total PAD, then the more big contribution of the tax and charges to the acceptance of PAD an area. This research contributes to the Kabupaten Malang government to better see the potential area which is owned to add value to the contribution of local tax and local charge as well as improve the performance of DPPKA. Key words : Contribution Analysis, Local Tax, Local Charges, Regional Income, PAD, Kabupaten Malang, Effectiveness, Effectiveness Ratio